Non-responders to egg grown influenza vaccine seroconvert after booster immunization with MDCK cell grown vaccine - Oxford, John S; Al-Jabri, Ali A; Lambkin, Robert; Palache, A.M; Fleming, D.M (Vaccine, 2003)
We have investigated whether ‘at risk’ subjects who did not respond serologically during a pre-study vaccination with a commercial egg grown influenza sub-unit vaccine would respond to a subsequent vaccination with either a single dose of MDCK cell grown influenza vaccine or a standard egg grown influenza vaccine containing the same virus strains. We studied 48 non-responder subjects with a mean age 67.5, range: 34–82 years. In this non-responder group the increased immune response that was detected after boosting with an MDCK cell derived vaccine response was variable and relatively modest, except for the A/Texas strain in the vaccine. The proportion of subjects, with an HI titre of ≥40 (protective antibody titre) increased from 50 to 83% (A/Texas strain), from 13 to 25% (B/Harbin strain) and from 38 to 46% (A/Wuhan strain). In comparison a booster vaccination with egg-derived influenza vaccine resulted in an increase immune response with an HI antibody titre ≥40 for two of the three strains, namely from 17 to 58% for the B/Harbin strain and from 8 to 33% for the A/Wuhan strain.